Evolution of pollen grain morphology in Amorimia and allies evidences the importance of palynological apomorphies and homoplasies in Malpighiaceae systematics - da Silva, Carolina Prandi [UNESP]; de Almeida, Rafael Felipe; Bellonzi, Talita Kely; Gasparino, Eduardo Custódio [UNESP] (Agentschap Plantentuin Meise, 2023)
Background and aims – Pollen grain morphology is an important morphological character for aiding the systematics of flowering plants. For Malpighiaceae, only a single unpublished palynological study has comprehensively sampled ca 60 of this family’s 75 currently accepted genera. To test the systematic relevance of pollen morphology in Amorimia and allies, we characterised the pollen morphology of these lineages. We scored, coded, and mapped 12 characters onto the most recent molecular phylogeny of Amorimia and allies. Material and methods – We sampled 13 species of Amorimia as ingroup and two species of Mascagnia and Ectopopterys soejartoi as outgroup. Pollen grains were acetolised, characterised, and measured using light microscopy and scanning electron microscopy. Pollen quantitative measurements were submitted to a PCA multivariate analysis. Additionally, quantitative and qualitative characters were scored and coded into 12 characters and mapped onto the molecular phylogeny of Amorimia and allies. Key results – Amorimia and allies are stenopalynous due to all species showing the same pollen type, with some subtle differences between the pollen grains, such as details of ornamentation, shape, size, and thickness of the pollen exine. However, the patterns of pollen grain evolution showed that few qualitative and apomorphic characters are informative for intrageneric distinction (i.e. type and number of apertures), and almost all quantitative and homoplastic characters analysed were informative at infrageneric levels within Malpighiaceae. Conclusion – Our results demonstrate that even though the pollen morphology characters of Amorimia and allies show subtle variation, both qualitative and quantitative apomorphic and/or homoplastic characters are highly informative for intra-and infrageneric levels in Malpighiaceae when analysed in a phylogenetic context.
Keywords: Ectopopterys; light microscopy; Malpighiales; Mascagnia; scanning electron microscopy; taxonomy